Análise das possíveis causas do criptorquidismo equino e suas implicações - Caceres, Amanda Manara (Universidade Estadual Paulista (Unesp), 2022)
A mammal is considered a cryptorchid when one or both testicles are not found in the scrotum after sexual maturity and can be found anywhere adjacent to the inguinal rings to the caudal pole of the kidneys. Several studies aimed at determining the etiology of cryptorchidism and understanding the anatomophysiological process of testicular migration is fundamental. In both humans and animals there is scientific evidence that this disease has genetic susceptibility and that the changes in genes are located in more than one locus. Allied to this, other possible causes are listed, such as environmental factors that can affect the correct hormonal functioning. Once there is this ectopy, there is also the perception of complications such as: inguinal hernias, acute abdomen, morphological and functional changes and even the development of neoplasms. Despite not having a well-described etiology, the diagnosis and treatment for this disease are known and are part of the routine of veterinarians. In this sense, cryptorchidism is of great importance to the equestrian environment and various breed associations around the world discuss what should be the conduct towards cryptorchid animals, since their use in reproduction generates divergent opinions.

Um mamífero é considerado criptorquídeo quando um ou os dois testículos não se encontram na bolsa escrotal após a maturidade sexual, podendo ser encontrados em qualquer lugar adjacente aos anéis inguinais até o pólo caudal dos rins. Diversos estudos objetivaram a determinação da etiologia do criptorquidismo e a compreensão do processo anatomofisiológico da migração testicular é fundamental. Tanto nos homens como nos animais há evidências científicas de que essa doença possui susceptibilidade genética e que as alterações nos genes estão localizadas em mais de um lócus. Aliado a isso são elencadas outras possíveis causas, como os fatores ambientais que podem afetar o funcionamento hormonal correto. Uma vez que há essa ectopia, há também a percepção de complicações como: hérnias inguinais, abdômen agudo, alterações morfológicas, funcionais e até o desenvolvimento de neoplasias. Apesar de não possuir etiologia bem descrita, o diagnóstico e o tratamento para essa doença são conhecidos e fazem parte da rotina de Médicos Veterinários. Neste sentido, o criptorquidismo é de grande importância para o âmbito equestre e várias associações de raças pelo mundo discutem qual deve ser a conduta perante aos animais criptorquidas, uma vez que o uso destes na reprodução gera opiniões divergentes.
Analysis of potential causes of equine cryptorchidism and its implications
Keywords: Cryptorchidism; Horses; Etiology; Reproduction; Criptorquidismo; Cavalos; Etiologia; Reprodução